ProtonMart - AI Driven E-Commerce Platform For Electronic Goods Using Collaberative Filtering Algorithm - Patil, Yash; Ashtikar, Samidha; Shirodkar, Sakshi; Dudhate, Krishna; Pandit, Shraddha V (International Journal of Computer Sciences and Engineering, 2024)
This research paper investigates the development of a Django-based e-commerce platform specializing in the sale of electronic goods, augmented with a user-based collaborative filtering algorithm for personalized product recommendations. In the competitive landscape of online retail, providing tailored recommendations to users is crucial for improving user engagement and driving sales. Leveraging Django framework, SQLite3 database, AJAX technology, and PayPal integration , this study explores the integration of collaborative filtering into the e-commerce framework to enhance user experience and boost sales. key features of this platform includes a search bar, brand and category filters, an administrative interface, shopping cart functionality, and integration with PayPal payment gateway. Subsequently, the research details the incorporation of a user-based collaborative filtering algorithm for product recommendations.